2012
DOI: 10.11646/zootaxa.3449.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The genus Bactrothrips in China (Thysanoptera: Idolothripinae): morphological and molecular data, and a key with two new species

Abstract: Seven species of Bactrothrips Karny are recognized from China, based on morphological and molecular data, including Bactrothrips elongatus n. sp. and B. furvescrus n. sp. Meiothrips baishanzuensis Duan & Li is a new synonym of B. brevitubus Takahashi, and Bactrothrips brevitubus zhamanus Han & Zhang is a new synonym of B. pictipes Haga & Okajima. Molecular evidence provides clear relationships in the N-J tree among species studied here. A generic diagnosis and key to Chinese Bactrothrips species ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The record is an error because the single species involved, Neosmerinthothrips brevicollis , is known only from the Seychelles, and the name was presumably confused with a similarly named species of Nesothrips . Keys have been published to the species from China in a few genera, including Bactrothrips , Gastrothrips , Meiothrips , and Ophthalmothrips (Dang and Qiao 2012a, Cao et al 2009, Dang and Qiao 2012b, Cao et al 2010). Recently, Dang et al (2013) reported some changes in nomenclature, including new synonyms, new combinations and new records from China.…”
Section: Systematics Of Idolothripinaementioning
confidence: 99%
See 4 more Smart Citations
“…The record is an error because the single species involved, Neosmerinthothrips brevicollis , is known only from the Seychelles, and the name was presumably confused with a similarly named species of Nesothrips . Keys have been published to the species from China in a few genera, including Bactrothrips , Gastrothrips , Meiothrips , and Ophthalmothrips (Dang and Qiao 2012a, Cao et al 2009, Dang and Qiao 2012b, Cao et al 2010). Recently, Dang et al (2013) reported some changes in nomenclature, including new synonyms, new combinations and new records from China.…”
Section: Systematics Of Idolothripinaementioning
confidence: 99%
“…Dang and Qiao (2012a) provided an identification key to these seven species, based on morphological and DNA barcoding data. The genus Bactrothrips is closely related to Megathrips , and differs from Megalothrips in usually having shorter maxillary stylets.…”
Section: Systematics Of Idolothripinaementioning
confidence: 99%
See 3 more Smart Citations